Use of a Liquid Supplement Containing 2 Human Milk Oligosaccharides: The First Double-Blind, Randomized, Controlled Trial in Pre-term Infants - Hascoët, Jean-Michel; Chevallier, Marie; Gire, Catherine; Brat, Roselyne; Rozé, Jean-Christophe; Norbert, Karine; Chen, Yipu; Hartweg, Mickaël; Billeaud, Claude (Frontiers in Pediatrics, 2022)
There is growing evidence supporting the benefit of human milk oligosaccharides (HMOs) on reducing risk of illnesses and improving immune function in newborn infants, but evidence in preterm infants is lacking. This randomized, double-blind, placebo-controlled trial (NCT03607942) of preterm infants evaluated effects of HMO supplementation on feeding tolerance, growth and safety in 7 neonatal units in France. Preterm infants (27-33 weeks’ gestation, birth weight <1700g) were randomized early after birth to receive HMO supplement (n=43) (2’FL and LNnT in 10:1 ratio (0.374 g/kg body weight/day)) or an isocaloric placebo (n=43) consisting of only glucose (0.140 g/kg/day) until discharge from the neonatal unit. Anthropometric z-scores were calculated using Fenton growth standards. Primary outcome was feeding tolerance, measured by non-inferiority (NI) in days to reach full enteral feeding (FEF) from birth in HMO vs. Placebo group (NI margin=+4 days). Mean number of days on intervention prior to FEF was 8.9 and 10.3 days in HMO and Placebo, respectively. Non-inferiority in time to reach FEF in HMO (vs. Placebo) was achieved (LS mean difference [95% CI] =-2.16 [-5.33,1.00]; upper bound of 95% CI